1999
DOI: 10.1046/j.1365-2265.1999.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of six months of treatment with a low‐dose of conjugated oestrogens in menopausal women

Abstract: Six months of treatment with 0.3 mg/day of conjugated equine oestrogen significantly lowers serum levels of total cholesterol and LDL-cholesterol without causing the adverse increases of triglycerides or factor VIIc, which were observed at higher doses. However, this low-dose treatment did not yield the maximal LDL-cholesterol lowering effect. Moreover, the positive effects of HRT on HDL-cholesterol, apolipoprotein A-I, lipoprotein (a) and plasminogen activator inhibitor-1 required at least the medium dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 54 publications
3
15
0
1
Order By: Relevance
“…However, whether these higher levels of prolactin depend on the composition/type of the used hormone therapy regimen is less clear. Our results are consistent with studies showing elevated levels of prolactin in postmenopausal women who used combined estrogen-progestin therapy (13)(14)(15), although some studies showed no significant effect of combined hormone therapy on blood prolactin levels (16)(17)(18). Likewise, in other studies the use of estrogens alone has shown to either increase (19,20) or not to have any significant influence on circulating prolactin levels (16,21,22).…”
Section: Discussionsupporting
confidence: 82%
“…However, whether these higher levels of prolactin depend on the composition/type of the used hormone therapy regimen is less clear. Our results are consistent with studies showing elevated levels of prolactin in postmenopausal women who used combined estrogen-progestin therapy (13)(14)(15), although some studies showed no significant effect of combined hormone therapy on blood prolactin levels (16)(17)(18). Likewise, in other studies the use of estrogens alone has shown to either increase (19,20) or not to have any significant influence on circulating prolactin levels (16,21,22).…”
Section: Discussionsupporting
confidence: 82%
“…In accordance, low-dose HRT regimens have been suggested for women in late postmenopausal period [2,5]. Adequate symptom control and beneficial effects on serum lipids, coagulation factors and bone have been observed with lower estrogen and progestogen doses in younger postmenopausal women with even better bleeding control than with higher doses [5][6][7][8]. However, it has not been studied whether lower estrogen doses would be sufficient for elderly women in particular, or whether the pharmacokinetics of estrogens or progestogens would be changed by ageing.…”
Section: Introductionmentioning
confidence: 84%
“…Touraine et al found a minimal change in prolactin after the onset of menopause in women taking hormone replacement therapy and a reduction in those who were not treated [17]. Most studies have shown that estrogen replacement therapy has little effect on serum prolactin [18].…”
Section: Menstrual Cycle and Menopausementioning
confidence: 96%